ADEQUATE RESPONSE FRAMEWORK TO 5G/IOT TECHNOLOGIES DISRUPTION FOR INCUMBENTS - Saxena, Rajesh Kumar (Digital Repository of Theses, 2023)
The advent of 5G/IoT technologies is being hailed as the premise of building the next industrial revolution and is being termed as Industry 4.0 which will impact the incumbents in unprecedented ways. The potential of Internet of Things (IoT) along with the converging technologies like cloud computing and 5G is being forecasted as a disruption wave that will spur innovation and can change the boundaries of industries. While the incumbents are bracing for this change, lot of uncertainty remains with regards to the prevalence of competitive business models, adoption of cloud services and engagement of the Ecosystem. The goal of this research is to enable organizations to position themselves well to provide adequate response to the 5G/IoT disruption wave. The research proposes analysis and synthesis of quantitative and qualitative data of existing theory, empirical data collected from 5G/IoT Ecosystem participants, 6 manufacturers, researchers, and consultants, along with testing the framework in case study conducted in real life setting of such incumbents. The research proposed to achieve this by explaining the causal relationship of three variables: the prevalence of competitive business models, adoption of cloud services to proliferate IoT offerings and engagement of the Ecosystem – that examine the research title – “Adequate Response Framework to 5G/IoT technologies disruption for incumbents”. The outcome of the research is an Adequate Response Framework that will help the incumbents to leverage 5G/IoT/Cloud technology convergence. It consists of an Innovation model that helps incumbents understand the key changes that are needed for each Influential Force and Research Dimension. Another aspect of this framework is the inclusion of a Decision Model that consists of core tenets and guidelines that helps incumbent understand how to realign the Influential forces to ensure that they leverage the technology advancements. Research has also developed a quad-classification model for incumbents to assess their maturity in terms of innovativeness in face of 5G/IoT technologies wave.